Professional identities in the archival field: a look located in the historical archives of Uruguay - Zuppardi, Leticia; Fuster, Yanet (Revista General de Información y Documentación, 2025)
The present contribution focuses on the professional identity of archivists, focusing on the historical archives of Uruguay to contribute to the understanding of the identity processes related to the archival professional group and the discussion on this topic, addressing a particular reality such as that of historical archives in Uruguay. Starting from the notion of field understood as a social space of action and influence in which social relations converge (Bourdieu, 1988), we seek to know what relationships are defined within this field by the possession or production of a specific form of capital. For this purpose, 16 semi-structured interviews were carried out based on an intentional sample of people who work in the field of archives in Uruguay, which was made up of twelve archivists and four people who graduated from other training. The testimonies were collected during the year 2023; through them, the field could be composed as a space where several disciplines converge, predominately archivists and historians. The findings show the tensions within the field and what factors can trigger them. The research made it possible to identify these tensions, in some cases from tangible elements (Law No. 19768, Archiving. Recognition of their professional status and regulation of their activity), which are recovered through the words of the professionals interviewed.